Online Learning in Digital Innovations - Mariono, Andi; Bachri, Bachtiar Syaiful; Kristanto, Andi; Dewi, Utari; Sumarno, Alim; Kholidya, Citra Fitri; Pradana, Hirnanda Dimas (Journal of Education Technology, 2021)
Students and lecturers cannot do direct learning. It is an obstacle in the delivery of material by the lecturer. The purpose of this research is to develop learning in the Digital Learning Learning Media course. This research uses development research—the model development used by ADDIE (Analyze, Design, Development, Implementation, Evaluation). The research subjects are three experts, which include material experts, media experts, learning design experts. The subject of the product trial is students. The methods used to collect data are observation, questionnaires, and tests. The instruments used to collect data are questionnaires and test sheets. The technique used to analyze the data is descriptive qualitative, quantitative, and statistical analysis. The results of the material expert test are 90% with the "very good" category. 90% "very good" learning design expert test, 90% media expert test in the "very good" category, and 95% student trials in the "very good" category. Based on data analysis, learning media for learning media is proven to be effective in learning. This finding proves a difference between the control class tcount value which is smaller than the experimental class tcount (3,558 < 5,610). The development of online learning can be helpful for students in carrying out learning caused by the limitations of distance and time. This bold course has innovative values, including independent online practice tests using camera simulators equipped with audio and video to make learning more interactive.